AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH AS FOREIGN LANGUAGE - Illananingtyas, Tenika (LPPM Universitas Kahuripan Kediri, 2023)
Abstract English is the most widely used language in international communication. English language skills of Indonesian people are currently considered to be in the low category. The ability to communicate in English, which is increasingly needed, has not been well developed through education. This research aims to describe the students' difficulties in speaking English as foreign language in Islamic University of Tribakti Lirboyo. This research has a descriptive qualitative approach. Data collection techniques include in-depth interviews, participant observation, and documentation. Data analysis techniques consist of condensing data, presenting data, and drawing conclusion. The research results show that there are some factors cause the students lack of speaking skill, those are: lack of vocabulary, incorrect pronunciation, can't find friends or partners in speaking, lack of self-confidence, lack of general knowledge, lack of speaking practice, fear of making mistakes, lack of use of words and grammar practice, low motivation, low participation, lazy reading, shyness, lack of use of dictionary, nervousness, fear of criticism. Keywords: students’ difficulties, speaking English, foreign language